Mediating Effect of Body Mass Index and Dyslipidemia on the Relation of Uric Acid and Type 2 Diabetes: Results From China Health and Retirement Longitudinal Study - Cheng, Fang; Li, Yanzhi; Zheng, Han; Tian, Lu; Jia, Hongying (Frontiers in Public Health, 2022)
Abstract Objective: This study assessed temporal relationships of serum uric acid (SUA) with blood glucose and determine the mediating effects of body mass index (BMI) and dyslipidemia on the relation of SUA and risk of type-2 diabetes. Methods: Participants aged ≥45 years were collected in 2011 and followed up until 2015. Cox proportional hazards regression with a robust variance estimator was performed to explore the association of SUA with the risk of diabetes, and cross-lagged path analysis was introduced to examine the temporal relationships between SUA and blood glucose. A mediation analysis was finally used to identify the mediating effect of BMI and dyslipidemia on the relation of SUA and the future risk of diabetes. Results: A total of 9020 participants were included with an average age of 58.59 years at baseline in 2011, and 53.6% of them were women. Linear dose-response relationship was identified by restricted spline cubic analysis between baseline SUA and follow-up blood glucose (The non-linear trend for fasting plasma glucose (FPG): β2=-0.71, P=0.52; for HbA1c: β2=-0.05, P=0.07; for risk of diabetes: β2=-0.12, P=0.39). And compared with the lowest quartiles of SUA, the adjusted risk ratios of diabetes were 1.00 (95%CI: 0.82-1.23), 1.08 (95%CI: 0.89-1.31), 1.37 (95%CI: 1.11-1.96) for quartile 2-4 (P-trend<0.01), respectively. Further additional adjustments for BMI or dyslipidemia, these ratios were not statistically significant. In addition, a unidirectional relationship from baseline SUA to follow-up FPG (ρ1=0.24, P=0.03) was furtherly confirmed using cross-lagged path analysis. After stratifying by genders, the above results were only significant in the women subgroup, we thus conducted a mediation analysis in women and found that the BMI and dyslipidemia partially mediated the effect of SUA on diabetes with a 23.05% and 18.82% mediating effect, respectively. Conclusions: These findings provide strong evidence that hyperuricemia preceded diabetes, and the effect of baseline SUA on follow-up type-2 diabetes was more pronounced among middle-aged and elderly Chinese women, especially in postmenopausal women, and this effect is partly mediated by BMI and dyslipidemia at baseline. Keywords: diabetes; BMI; uric acid; dyslipidemia; mediation effect